THE EFFECTIVENESS OF USING BOT TELEGRAM IN TEACHING READING NARRATIVE TEXT AT THE TENTH GRADE OF SMAN 1 GROGOL KEDIRI - Sulistyanto, Irwan; Prellany, Nindy (Pusat Penelitian dan Pengembangan Rekarta Mataram, 2020)
Bot Telegram as teaching media, is also used as a tool to connect the classroom to the experts and educators around the world who are interested in the use of social media in educational environments. Bot Telegram is effective to be used in teaching reading at the tenth grades of SMAN 1 Grogol Kediri. This experimental research uses post-test only control group design. Two classes are used as research subjects, they are; experimental class (N = 36) and control class (N = 36). Experimental class is taught by using Bot telegram, whereas control class which is not being taught using Bot Telegram. Writing test is used to collect the data. The result shows that the mean of experimental class is higher than the control class (86.89 > 79.89) while the analysis of independent-samples t-test reveals that the experimental group outperforms the control group in reading achievement. The results significance value (sig. 2 tailed) .000 is lower than alpha level of 5% or 0.05. Thus, it can be concluded that Bot Telegram is effective to be used in teaching reading especially in narrative text.